Analisis Behavior Contract Dalam Pembelajaran Pada Anak Madrasah Ibtidaiyah Negeri (MIN) I Kota Kediri - Ahmad Khoirul Mustamir; Muslimin (Institut Agama Islam Tribakti Kediri, 2021)
Behavioral Contract as an attempt to change certain behaviors in counseling. This technique is used to help solve the problem of maladaptive behavior in clients / counseling who want to change the behavior for the better at State Elementary School I Kediri. The focus is on motivating students to complete homework. Efforts to complete this research using observation techniques and in-depth interviews with stakeholders at State Elementary School I Kediri. The result is that the application of the behavior contract technique for students who have this problem has seen a good change. Students feel happy doing homework from all subjects given at State Elementary School I Kediri teachers. [Behavioral Contract sebagai suatu usaha mengubah perilaku tertentu pada konseling. Teknik ini digunakan untuk membantu menyelesaikan permasalahan perilaku maladaptif pada diri klien/konseling yang berkeinginan merubah perilaku tersebut menjadi lebih baik di MIN I Kota Kediri. Fokusnya adalah memotovasi siswa dalam menyelesaikan pekerjaan rumah. Usaha menyelesaikan penelitian ini dengan menggunakan teknik observasi dan wawancara mendalam kepada stakeholder di MIN I Kota Kediri. Hasilnya penerapan teknik behavior contract siswa yang memiliki masalah tersebut sudah terlihat perubahan yang baik. Siswa merasa senang mengerjakan pekerjaan rumah dari seluruh mata pelajaran yang diberikan guru-guru MIN I Kota Kediri]